Case report: From monkeypox pharyngitis to myopericarditis and atypical skin lesions - Sanromán Guerrero, María Ascensión; Sánchez, Elena Hernández; Ruanes, Belén de Nicolás; Fernández-González, Pablo; Ugalde, Sonia Antoñana; Leal, Alejandra González; Fernández, Marcelo Sanmartín; Rodríguez, Jose Javier Alarcón; Martinez Garcia, Laura; Escudero, Rosa; Méndez, Maria Ángeles Fernández; Zamorano Gómez, Jose Luis; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: A global outbreak of Human Monkeypox Virus (HMPXV), first identified in May 2022, was declared a Health Emergency of International Concern on 23 July 2022. Prior to the global outbreak, monkeypox cases were mostly confined to countries in central and West Africa, where the virus is endemic. Close contact, mainly sexual contact, is supposed to be the main route of transmission and it is remarkable that the incidence is higher in men that have sexual relationships with men. Case Summary: A 40 year-old Caucasian male arrived at the emergency department with complaints of oppressive epigastric pain extending to the chest after a diagnosis of pharyngitis suspected to be caused by the Human Monkeypox Virus. Based on the clinical symptoms, physical examination, serum cardiac biomarkers and electrocardiographic findings, he was diagnosed of myopericarditis. The real-time PCR for human Monkeypox in skin lesions, urine, plasma and oropharyngeal swab was positive. The peak of troponin I was 20.6 ng/ml and the electrocardiogram showed an upward concavity in the ST segment in diffuse leads in agreement with the previous diagnosis. The presence of edema, subepicardial and mesocardial late gadolinium enhancement and increased values on T1 mapping in the cardiac MRI were in agreement with the diagnosis of myopericarditis. An antiviral treatment with tecovirimat was started with excellent tolerability. After 6 days, the patient was totally recovered and was discharged. Discussion: To our knowledge, this is one of the first reported cases of myopericarditis due to Human Monkeypox infection, which was confirmed by a cardiac MRI following modified Lake Louise criteria. The short span between the onset of the mucocutaneous symptoms and the myocardial damage suggests a pathogenic association. Furthermore, the active viral replication in plasma samples, as well as the negative results on real-time PCR for other viruses supports this clinical association.